2022
DOI: 10.1155/2022/4258124
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of the Antioxidant and Antidiabetic Potential of Nelumbo nucifera Gaertn. and Nymphaea lotus L. var. pubescens (Willd.)

Abstract: Background. Nelumbo nucifera Gaertn. and Nymphaea lotus L. var. pubescens (Willd.) are both aquatic rhizomatous perennial plants mostly found in the tropical region of Nepal, India, Bangladesh, China, and Eastern Asia. Nymphaea pubescens and Nelumbo nucifera plants are famous for their different biological activities such as antidiabetic, antioxidant, hepatoprotective, antidiarrheal, and anti-inflammatory properties. Objective. The present study majorly focused on the determination of in vitro antioxidant and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Compounds 1, 2, 4 and 6 were isolated and identified as components in N. pubescens petals for the first time. Previous studies reported that 4 was found in the N. stellata flowers [37], 3 and 5 were found in the N. pubescens petals [18,38,39], while 6 was found in the N. stellata flowers [40] and the N. Alba flowers [41] and leaves [42]. Compound 4 has been previously isolated from Rhamnus nakaharai Hayata (Rhamnaceae) and reported to inhibit PDE5 enzymes isolated from the lungs and hearts of male guinea pigs with an IC 50 value of 86.9 µM [43], 3 and 5 have been previously isolated from Anaxagorea luzonensis and reported to inhibit PDE5 enzymes isolated from the mice lungs [14], while 1, 2, and 6 has not previously been reported for their effects on PDE5.…”
Section: Discussionmentioning
confidence: 92%
“…Compounds 1, 2, 4 and 6 were isolated and identified as components in N. pubescens petals for the first time. Previous studies reported that 4 was found in the N. stellata flowers [37], 3 and 5 were found in the N. pubescens petals [18,38,39], while 6 was found in the N. stellata flowers [40] and the N. Alba flowers [41] and leaves [42]. Compound 4 has been previously isolated from Rhamnus nakaharai Hayata (Rhamnaceae) and reported to inhibit PDE5 enzymes isolated from the lungs and hearts of male guinea pigs with an IC 50 value of 86.9 µM [43], 3 and 5 have been previously isolated from Anaxagorea luzonensis and reported to inhibit PDE5 enzymes isolated from the mice lungs [14], while 1, 2, and 6 has not previously been reported for their effects on PDE5.…”
Section: Discussionmentioning
confidence: 92%
“…[213] The investigation focused on the in vitro antioxidant and anti-diabetic characteristics, using PNPG as a substrate to inhibit glucosidase with IC 50 values of 66.32 � 4.35. [214] Furthermore, the extract of N. nucifera Gaertn lowers blood sugar levels and improves glucose tolerance in healthy rabbits. In-vivo studies on rat hemidiaphragm have shown that administering test drugs to animals can significantly enhance the effects of insulin, because the skeletal muscles become more responsive to endogenous insulin, leading to improved peripheral glucose utilization.…”
Section: Aldose Reductase Inhibitormentioning
confidence: 99%
“…Kaempferol and isorhamnetin confirmation the repressive action with IC 50 values of 5.6 and 9.0 μM, respectively [213] . The investigation focused on the in vitro antioxidant and anti‐diabetic characteristics, using PNPG as a substrate to inhibit glucosidase with IC 50 values of 66.32±4.35 [214] . Furthermore, the extract of N. nucifera Gaertn lowers blood sugar levels and improves glucose tolerance in healthy rabbits.…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…An analysis was conducted to determine the α-glucosidase inhibitory activity of the extract and fractions. The analysis was conducted using the standard method, with some minor modifications [13]. In a 96-well plate, a reaction mixture was preincubated at 37 degrees Celsius for fifteen minutes.…”
Section: In Vitro Antidiabetic Assay α-Amylase Inhibitory Assaymentioning
confidence: 99%